EXPERIENCE OF FOREIGN PRESCHOOL EDUCATIONAL ORGANIZATIONS IN THE FIELD OF EDUCATION OF PRESCHOOL CHILDREN - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
In this article, on the basis of a comparative analysis, the best practices of preschool education and upbringing in foreign countries are studied. Information is presented on the forms and conditions of preschool education in the main developed Western countries. Opinions on the content of ongoing reforms and their effectiveness are emphasized.